PENGARUH PERUBAHAN TEMPERATUR DAN PENAMBAHAN AGREGAT KACA TERHADAP KUAT TEKAN BETON - Taufiq, Ahmad (Universitas Negeri Surabaya, 2023)
Fires often occur in various countries, especially in Indonesia. The fire disaster caused damage to building materials, one of which was concrete structures. Concrete is a material that is generally used for a structure in a building. This research was conducted to determine the difference in compressive strength of concrete when burning and before burning. The method used in this study was an experimental method, namely concrete cubes aged 28 days, after which they were fired at 100C and 200C. The results of this study showed a decrease in the compressive strength of concrete at 100C and 200C. The compressive strength of concrete also decreases when the concrete is mixed with glass aggregate at temperatures of 100C and 200C.